De-tabooing dying control - a grounded theory study - Thulesius, Hans O (BioMed Central, 2013)
BACKGROUND: Dying is inescapable yet remains a neglected issue in modern health care. The research question in this study was “what is going on in the field of dying today?” What emerged was to eventually present a grounded theory of control of dying focusing specifically on how people react in relation to issues about euthanasia and physician-assisted suicide (PAS). METHODS: Classic grounded theory was used to analyze interviews with 55 laypersons and health care professionals in North America and Europe, surveys on attitudes to PAS among physicians and the Swedish general public, and scientific literature, North American discussion forum websites, and news sites. RESULTS: Open awareness of the nature and timing of a patient’s death became common in health care during the 1960s in the Western world. Open dying awareness contexts can be seen as the start of a weakening of a taboo towards controlled dying called de-tabooing. The growth of the hospice movement and palliative care, but also the legalization of euthanasia and PAS in the Benelux countries, and PAS in Montana, Oregon and Washington further represents de-tabooing dying control. An attitude positioning between the taboo of dying control and a growing taboo against questioning patient autonomy and self-determination called de-paternalizing is another aspect of de-tabooing. When confronted with a taboo, people first react emotionally based on “gut feelings” - emotional positioning. This is followed by reasoning and label wrestling using euphemisms and dysphemisms - reflective positioning. Rarely is de-tabooing unconditional but enabled by stipulated positioning as in soft laws (palliative care guidelines) and hard laws (euthanasia/PAS legislation). From a global perspective three shapes of dying control emerge. First, suboptimal palliative care in closed awareness contexts seen in Asian, Islamic and Latin cultures, called closed dying. Second, palliative care and sedation therapy, but not euthanasia or PAS, is seen in Europe and North America, called open dying with reversible medical control. Third, palliative care, sedation therapy, and PAS or euthanasia occurs together in the Benelux countries, Oregon, Washington and Montana, called open dying with irreversible medical control. CONCLUSIONS: De-tabooing dying control is an assumed secular process starting with open awareness contexts of dying half a century ago, and continuing with the growth of the palliative care movement and later euthanasia and PAS legislation.